Pengaruh Gaya Kepemimpinan Suportif, Palayanan dan Fasilitas Belajar terhadap Prestasi Belajar Taruna Lalu Lintas Udara Angkatan VIII untuk Mengoptimalkan Daya Serap Lulusan Politeknik Penerbangan Surabaya - Aulia Regia S.P; Bambang Wasito; Sri Lestari; R. Moh. Radix Agustiono (Jurnal Penelitian)
This study is entitled "Analysis of the Effect of Supportive Leadership Style, Learning Services and Facilities on Learning Achievement of Air Traffic Youth Class VIII to optimize the Absorption of Graduates at Aviation Polytechnic of Surabaya Supportive leadership style influences the learning achievement of cadets at Aviation Polytechnic of Surabaya Services affect the learning achievements of cadets Air Traffic Surabaya Flight Polytechnic. Learning facilities have an effect on the learning achievements of cadets at Aviation Polytechnic of Surabaya Air Traffic cadets learning achievements affect the absorption capacity of Surabaya Aviation Polytechnic graduates.